Penyuluhan Penggunaan Pupuk Organik Guna Peningkatan Kapasitas Pertanian di Desa Gudo, Kecamatan Gudo, Kabupaten Jombang - Sudarso, Sudarso; Tri, Bambang; Ryadin, Fahmy; Sholeh, M.; Handayani, Budi (Unity Academy, 2025)
The scarcity of subsidized fertilizers has become an annual issue that significantly affects the productivity of farmers in Indonesia, including those in Gudo Village, Gudo District, Jombang Regency. Dependence on chemical fertilizers worsens the situation when supplies are limited and prices soar. Organic fertilizer offers a more environmentally friendly alternative solution and can be processed from locally available materials. This community service activity aims to improve farmers’ understanding of the benefits of organic fertilizers and to encourage the adoption of sustainable agriculture practices.The outreach activity was conducted on April, 2025, at the farm area and was attended by 10 farmers. The materials presented covered the benefits of organic fertilizers, the use of agricultural waste, and the urgency of diversifying nutrient sources. Evaluation was conducted through observation and questionnaires. Results showed that 85% of participants were satisfied with the content and delivery. The activity built new awareness about the potential of organic fertilizers and opened opportunities for further training. This initiative marks an initial step in strengthening farmers' capacity toward a more independent and sustainable agricultural system.